Knowledge and attitude of accepting COVID-19 vaccine booster doses and third doses among postpartum women in Palembang, Indonesia - Dian Lestari; Aprilina Aprilina; Sukarjo Sukarjo (Malahayati International Journal of Nursing and Health Science, 2023)
Background: Since the discovery of Covid-19, scientific developments, policies, and programs regarding Covid-19 have changed rapidly. In 2022 the Covid-19 vaccine arrived at the second booster. In Indonesia, various policies related to Covid-19 are also experiencing very rapid adjustments, such as the policy for travelling using public transportation, planes, trains, and ships that require the completeness of the Covid-19 vaccine up to boosters. These regulations make the Covid-19 vaccination a necessity that seems forced. Pregnant and postpartum women are also not free from the target of giving Covid-19. Various theories and research have proven that knowledge is related to attitude. Following this theory, knowledge and attitudes will align with the completeness of Covid-19. So if positive knowledge and attitudes affect the completeness of the Covid-19 vaccine, then it will not be affected by the Covid-19 vaccination obligation policy required by the Indonesian government.Purpose: To find out the relationship between Knowledge and attitude of accepting COVID-19 vaccine booster doses and third doses among postpartum women in Palembang, IndonesiaMethod: This study was quantitative. The design was analytical with a cross-sectional approach. The study samples consisted of 38 postpartum mothers in Independent Practice Midwife at Palembang. The complications of postpartum mothers were excluded. The sampling technique was accidental sampling.Results: There is no relationship between knowledge and accepting COVID-19 vaccine booster doses and third doses (p=0.348), but in the analysis, there is a relationship between attitude towards vaccination readiness and accepting COVID-19 (p=0.003), there is a relationship between attitude towards government policy and completeness of vaccination Covid-19 (p=0.004), there is a relationship between attitudes towards vaccines and accepting COVID-19 (p=0.015)Conclusion: There is no relationship between knowledge and accepting COVID-19, and there is a relationship between attitude and accepting COVID-19